2022
DOI: 10.1021/acsnano.1c11166
|View full text |Cite
|
Sign up to set email alerts
|

Deformation-Induced Phase Transformations in Gold Nanoribbons with the 4H Phase

Abstract: The mechanical stability of metallic nanomaterials has been intensively studied due to their unique structures and promising applications. Although extensive investigations have been carried out on the deformation behaviors of metallic nanomaterials, the atomic-scale deformation mechanism of metallic nanomaterials with unconventional hexagonal structures remains unclear because of the lack of direct experimental observation. Here, we conduct an atomic-resolution in situ tensile-straining transmission electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…88 Surface stress may also trigger the transformation from hcp to fcc phases during the plastic deformation process. 254 These phenomena in phase transformation 255 were also observed for metals with morphologies other than 2D nanostructures 256,257 or in the bulk form. 258 Silver may form thick and triangular 2D nanostructures because of the formation of twin defects.…”
Section: Group 11 Metal Elements (Au and Ag)mentioning
confidence: 75%
See 1 more Smart Citation
“…88 Surface stress may also trigger the transformation from hcp to fcc phases during the plastic deformation process. 254 These phenomena in phase transformation 255 were also observed for metals with morphologies other than 2D nanostructures 256,257 or in the bulk form. 258 Silver may form thick and triangular 2D nanostructures because of the formation of twin defects.…”
Section: Group 11 Metal Elements (Au and Ag)mentioning
confidence: 75%
“…, Ag) can induce a transformation from hcp to fcc crystalline phases . Surface stress may also trigger the transformation from hcp to fcc phases during the plastic deformation process . These phenomena in phase transformation were also observed for metals with morphologies other than 2D nanostructures , or in the bulk form …”
Section: Materials Developments Of 2d Metal Nanosheetsmentioning
confidence: 80%
“…19,63 In a recent study, together with Han, Liao, and other co-workers, we investigated the phase transformation behavior of Au nanoribbons with unconventional 4H phase under external mechanical stress. 26 After the deformation of a 4H-Au nanoribbon induced by tensile strain (Figure 2e,f), a 4H-to-fcc phase transformation was observed in the fracture tip, along with the formation of twin boundaries (Figure 2g). Song et al demonstrated a reversible 2H−1T′ phase transformation of MoTe 2 via tensile strain generated from an atomic force microscope (AFM) tip.…”
Section: Plasma Irradiationmentioning
confidence: 99%
“…Specifically, the identification of the structural evolution of unconventional-phase materials would lead to deep fundamental understanding of their structural stabilities and transformation mechanisms, providing important guidance to the stabilization strategy of unconventional phases and the exploration of their future applications. 1,19,20 Taking Au as an example, the transformation mechanisms from the unconventional 4H phase to the thermodynamically stable face-centered cubic (fcc) phase in Au nanostructures under diverse conditions, e.g., heating, 24 high pressure, 25 deformation, 26 electron beam irradiation, 27 etc., have been systematically investigated with the aid of various in situ techniques. Moreover, fine control over the transformation of unconventional-phase starting materials also represents an efficient approach toward the preparation of unconventional structures that normally cannot be obtained from conventional starting materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation